Cobalt ferrite nanoparticles under high pressure - Saccone, Fabio Daniel (2015)
We report by the first time a high pressure X-ray diffraction and Raman spectroscopy study of cobalt ferrite (CoFe2O4) nanoparticles carried out at room temperature up to 17 GPa. In contrast with previous studies of nanoparticles, which proposed the transition pressure to be reduced from 20–27 GPa to 7.5–12.5 GPa (depending on particle size), we found that cobalt ferrite nanoparticles remain in the spinel structure up to the highest pressure covered by our experiments. In addition, we report the pressure dependence of the unit-cell parameter and Raman modes of the studied sample. We found that under quasi-hydrostatic conditions, the bulk modulus of the nanoparticles (B0 = 204 GPa) is considerably larger than the value previously reported for bulk CoFe2O4 (B0 = 172 GPa). In addition, when the pressure medium becomes non-hydrostatic and deviatoric stresses affect the experiments, there is a noticeable decrease of the compressibility of the studied sample (B0 = 284 GPa). After decompression, the cobalt ferrite lattice parameter does not revert to its initial value, evidencing a unit cell contraction after pressure was removed. Finally, Raman spectroscopy provides information on the pressure dependence of all Raman-active modes and evidences that cation inversion is enhanced by pressure under non-hydrostatic conditions, being this effect not fully reversible.